Experimental study on compressive properties of steel fibre concrete. Issue 4 (May 2019) - Liu, Yanjie; Ding, Lin; Yang, Tianyu; Wang, Xunan
Abstract: The uniaxial compression tests were carry out in 5 groups steel fibre concrete specimens for 3 kinds of curing age, and the effect of steel fibre incorporation rate and curing age was studied on the compressive properties of concrete. The results show that the compressive strength of steel fibre reinforced concrete increases with the increase of the ratio of steel fibre. When the steel fibre incorporation rate is constant, the compressive strength of the steel fibre has a small increase with the growth of the curing age. The addition of steel fibre can effectively improve the crack resistance and toughness of concrete. With the addition of steel fibre, plastic deformation ability of concrete is enhanced, and the ultimate destruction form of concrete is the shear failure with obvious oblique cross section.